Contrasting trends in two Black-tailed Godwit populations:a review of causes and recommendations - Gill, Jennifer A.; Langston, Rowena H.W.; Alves, José A.; Atkinson, Philip W.; Bocher, Pierrick; Cidraes Vieira, Nuno; Crockford, Nicola J.; Gélinaud, Guillaume; Groen, Niko; Gunnarsson, Tómas G.; Hayhow, Becca; Hooijmeijer, Joslyn; et al. (2007)
In recent decades, the West European population of Black-tailed Godwits, Limosa limosa limosa, has declined in size at a quite alarming rate, while the Icelandic population, L. l. islandica, has undergone a rapid increase in population size. These two populations have been the subject of a great deal of research, much of which has been focused on understanding the causes and consequences of the contrasting population trends. In 2007, a workshop was held during the annual conference of the International Wader Study Group at La Rochelle, France, with the aims of identifying the likely causes of the population changes and providing recommendations for future actions to improve the conservation of both populations. The available evidence strongly suggests that changes in productivity as a consequence of agricultural intensification are the most likely driver of the decline in L. l. limosa, although the concentration of much of the population in just a few sites in winter and spring is likely to exacerbate their vulnerability to future habitat changes. Agricultural and climatic changes are implicated in the expansion of L. l. islandica, and the availability of both intertidal mudflats and wet grasslands as foraging habitats appears to be very important across much of the winter range of this population. A series of recommendations for actions to conserve both populations are provided, including improving agricultural land management and protecting key passage and winter sites and habitats.